A ring-width-based reconstruction of June–July minimum temperatures since AD 1245 from white spruce stands in the Mackenzie Delta region, northwestern Canada - Porter, Trevor J.; Pisaric, Michael F.J.; Kokelj, Steven V.; deMontigny, Peter (Quaternary Research, 2013)
This is the accepted manuscript of an article published by Elsevier. We present a reconstruction of June-July minimum temperatures since AD 1245 for the Mackenzie Delta region based on a 29-site network of white spruce (Picea glauca) ring-width series. Most, but not all trees experienced a divergent temperature-growth response, similar to the divergence that has affected other white spruce trees across Yukon and Alaska. However, divergence in the study region began as early as AD 1900 and we have documented our methods to avoid including divergent signals in the reconstruction. Calibration/verification testing based on local temperature data, and multi-century coherence with nearby and large-scale temperature proxy records, confirm our reconstruction is robust. The reconstruction shows cool conditions in the late 13th, early 18th and early 19th centuries, corresponding with solar minima and increased volcanism. These cool periods are interrupted by warm periods consistent with early to mid-20th-century warmth. The late 20th century is the warmest interval, and the last decade is estimated to be 1.4°C warmer than any decade before the mid-20th century. The reconstructed climate history corroborates other proxy-based inferences and supports the notion that high-latitude regions such as the Mackenzie Delta have experienced rapid warming in recent decades that is exceptional in the last eight centuries. This work received funding and logistical support from Aboriginal Affairs and Northern Development Canada, Cumulative Impact Monitoring Program and Northern Scientific Training Program; the Natural Sciences and Engineering Research Council of Canada; and the Polar Continental Shelf Program.